Pengaruh Sereal Instan Povita (Ubi Jalar Ungu Dan Kacang Hijau) pada Penurunan Glukosa Darah - Amran, Mayasari; Siregar, Afriyana Siregar; Nilawati, Nurul Salasa (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2024)
Diabetes mellitus (DM) is defined as a metabolic disorder with signs of elevated blood glucose levels (hyperglycemia). This condition arises from chronic metabolic disorders due to insufficient insulin production by the pancreas. Another result is difficulty in metabolizing carbohydrates, fats, and proteins. This phenomenon arises due to the irregularity of insulin secretion. The incidence of diabetes mellitus in South Sumatra increased from 0.9% to 1.3%. Translated with DeepL.com (free version) Methods: Researchers conducted 2 stages of research, namely with a non-factorial total random design and a Quasi-Experimental research research approach with pretest-posttest with control design. Results: The results of the organoleptic test conducted on the cookie formulas Formula 1, Formula 2, Formula 3, and Formula 4 showed that the majority of panelists stated that they liked Formula 1 in terms of aroma, color, and taste. According to the Friedman test, no statistically significant differences were seen in terms of color (p = 0.011), aroma (p = 0.000), texture (p value = 0.097), and taste (p = 0.000). Macronutrient intake in the treatment group was adequate both before and after cereal administration. Specifically, the percentage of calories, protein, fat, carbohydrates, and fiber were 66.7%, 60%, 56.7%, 76.7%, and 73.3%, respectively. Calorie consumption in the comparison group was 66.7%, protein intake was 83.3%, carbohydrate intake was 70%, fat intake was 66.7%, and fiber intake was 60.0%. In the treatment group, the majority of participants had adequate micronutrient intake both before and after consuming the cereal. Specifically, 73.3% of participants had adequate fiber intake and 73.3% had acceptable magnesium intake. The comparison group also had an adequate amount of fiber, with 60% fiber and 63.3% magnesium. Conclusion: The research findings show that Povita Instant cereal has a significant effect on blood glucose levels in patients with diabetes mellitus at Dr. H.Mohamad Rabain Muara Enim Hospital. Therefore, it can be recommended as a suitable snack for people with diabetes.